Cardiovascular Consequences of Skeletal Muscle Impairments in Breast Cancer - Gabriel H. Zieff; Chad W. Wagoner; Craig Paterson; Patricia Pagan Lassalle; Jordan T. Lee (MDPI AG, 2020)
Breast cancer survivors suffer from disproportionate cardiovascular disease risk compared to age-matched controls. Beyond direct cardiotoxic effects due to treatments such as chemotherapy and radiation, breast-cancer-related reductions in skeletal muscle mass, quality and oxidative capacity may further contribute to cardiovascular disease risk in this population by limiting the ability to engage in aerobic exercise-a known promoter of cardiovascular health. Indeed, 20-30% decreases in peak oxygen consumption are commonly observed in breast cancer survivors, which are indicative of exercise intolerance. Thus, breast-cancer-related skeletal muscle damage may reduce exercise-based opportunities for cardiovascular disease risk reduction. Resistance training is a potential strategy to improve skeletal muscle health in this population, which in turn may enhance the capacity to engage in aerobic exercise and reduce cardiovascular disease risk.